Gyrokinetic simulations in stellarators using different computational domains. (19th October 2021) - Sánchez, E.; García-Regaña, J.M.; Bañón Navarro, A.; Proll, J.H.E.; Mora Moreno, C.; González-Jerez, A.; Calvo, I.; Kleiber, R.; Riemann, J.; Smoniewski, J.; Barnes, M.; Parra, F.I.
Abstract: In this work, we compare gyrokinetic simulations in stellarators using different computational domains, namely, flux tube (FT), full-flux-surface (FFS), and radially global (RG) domains. Two problems are studied: the linear relaxation of zonal flows (ZFs) and the linear stability of ion temperature gradient (ITG) modes. Simulations are carried out with the codes EUTERPE, GENE, GENE-3D, and stella in magnetic configurations of LHD and W7-X using adiabatic electrons. The ZF relaxation properties obtained in different FTs are found to differ with each other and with the RG result, except for sufficiently long FTs, in general. The FT length required for convergence is configuration-dependent. Similarly, for ITG instabilities, different FTs provide different results, but the discrepancy between them diminishes with increasing FT length. FFS and FT simulations show good agreement in the calculation of the growth rate and frequency of the most unstable modes in LHD, while for W7-X differences in the growth rates are found between the FT and the FFS domains. RG simulations provide results close to the FFS ones. The radial scale of unstable ITG modes is studied in global and FT simulations finding that in W7-X, the radial scale of the most unstable modes depends on the binormal wavenumber, while in LHD no clear dependency is found.